PENGARUH KUALITAS PRODUK, CITRA MEREK TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN HANDPHONE SAMSUNG (Studi pada Mahasiswa Fakultas Ekonomika dan Bisnis Unisbank Semarang Pengguna Handphone Samsung) - Gunung Setyo Drajat, 04.05.51.0022; Soliha, Euis (Students Journal of Economic and Management, 2016)
The purpose of this study was to analyze the effect of product quality and brand image to customer satisfaction and customer loyalty Samsung mobile phone. The population in this study are all Samsung mobile phone users. The samples in this study using purposive sampling, that the sampling technique with a specific purpose. Consideration of the samples in this study were students of the Faculty of Economics and Business Unisbank Semarang who have been using mobile phone Samsung at least six months. The analytical tool used is multiple linear regression analysis. The results of the analysis can be concluded that: The product quality positively affects customer satisfaction. Brand image positively affects customer satisfaction. Product quality positively affects customer loyalty. Brand image positively affects customer loyalty. Customer satisfaction has positive effect on customer loyalty. Keywords: product quality, brand image, customer satisfaction and customer loyalty